Bicomplex Tetranacci and Tetranacci-Lucas Quaternions - Soykan, Yüksel (Communications in Mathematics and Applications, 2020)
In this paper, we introduce the bicomplex Tetranacci and Tetranacci-Lucas quaternions. Moreover, we present Binet’s formulas, generating functions, and the summation formulas for those bicomplex quaternions.